Programa con voluntariado universitario para el fomento de la lectura por placer entre niños y adolescentes - Goikoetxea, Edurne; Reus, Manolo; Rodríguez, Laura; Arbaiza, Aitor (Huarte de San Juan. Filología y Didáctica de la Lengua, 2018)
This paper presents a volunteer program called Un libro contigo (A book with you) aimed at encouraging reading for pleasure or voluntary reading in children and adolescents. While there is agreement that voluntary for pleasure is one of the most valuable habit for its academic, intellectual and emotional benefits, there are obstacles to its realization in schools and families. Some of the obstacles that explain the reduced practice of reading for pleasure are mentioned, and a volunteer program created to collaborate in overcoming this situation is described. The objectives and components, participants, format, and evaluation of the program are presented, as well as some future challenges.